Urban distribution of Phlebotominae in a cutaneous leishmaniasis focus, Argentina - Salomón, Oscar Daniel (2008)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.